Comparison of the Complications of Colon Anastomosis and Related Factors in Emergency versus Elective Surgery - MR Zandipour; A Elyasi; J Manouchehri; MA Rasouli; B Zareie (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2024)
Background and Objective: Colon surgery is one of the important operations in the abdominal area, but according to the type and conditions of surgery and clinical conditions, they can have different results and complications. The aim of this study is to determine the complications and related factors in patients who underwent colon anastomosis in emergency and elective surgery. Methods: In this cross-sectional study, 70 patients over 18 years of age and in need of colon anastomosis, who visited Kowsar Hospital in Sanandaj in 2017-2020, were examined in both emergency and elective groups. The patients were examined for complications such as bleeding, abscess, anastomotic leak, partial obstruction, fistula, and death, and the patients were followed up for six months, and if any of the complications occurred, the patient was hospitalized and examined further. Findings: The patients of the two groups did not have statistically significant differences in terms of demographic variables of age and gender, and surgery time. The highest frequency of the cause of surgery in the emergency group was volvulus in 10 cases (28.7%) and in the elective group was colon cancer in 26 cases (74.3%); in this regard, a statistically significant difference was observed between the two groups (p<0.001). The most common anastomosis site in the emergency group was the descending colon region (13 [37.1%]) and in the elective group was the ascending colon region (14 [40%]). The most common complications during and after anastomosis surgery include bleeding, infection, anastomosis leak and death, and the death rate in the emergency group was 7 people. The most common cause of death was peritonitis with 3 cases, followed by cardiorespiratory failure, embolism, disseminated intravascular coagulation and COVID-19 with peritonitis, with 1 case each. The history of hypertension and intraoperative bleeding had a statistically significant relationship with the incidence of colon anastomosis complications in both study groups (p=0.01). Conclusion: Based on the results of this study, the incidence of anastomosis complications is higher in the emergency group, including increased intraoperative bleeding, and in emergency situations, the decision to perform primary anastomosis should be made according to the patient's clinical conditions.